Understanding the means of communication between nurses and resident physicians in the modern world: A community-based university hospital survey results - Tarek Haykal; Ragheed Al-Dulaimi; Shima Sidahmed; Ravi Velagapudi; Noelle Fahr; Seif Saeed; Ghassan Bachuwa (Greater Baltimore Medical Center, 2020)
In a hospital setting, nurses and physicians are the two main caregivers for admitted patients. Their communication is an important driver of positive teamwork and ensures proper patient safety and a high level of patient care. In a hospital with a large internal medicine residency program, where the main communication between nurses and residents is by phone calls, the excess number of phone calls received, especially for non-urgent patient-related matters, can be disruptive and cause fatigue and burnout. Alternative means of communication have been reported, namely using the electronic medical records to try and create new means of communication and to decrease the burden of direct communication for non-urgent matters. This manuscript describes the results of a survey administered in an attempt to understand the communication between residents and nurses in the setting of a new communication tool created within the electronic medical records.